The effectiveness of systematic pain assessment on critically ill patient outcomes: A randomised controlled trial - Georgiou, Evanthia; Paikousis, Lefkios; Lambrinou, Ekaterini; Merkouris, Anastasios; Papathanassoglou, Elizabeth (My University, 2020)
Background: Evidence suggests that critically ill patients’ pain may still be underestimated. Systematic approaches to pain assessment are of paramount importance for improving patients’ outcomes. Objectives: To investigate the effectiveness of a systematic approach to pain assessment on the incidence and intensity of pain and related clinical outcomes in critically ill patients. Methods: Randomized controlled study with consecutive critically ill patients allocated to either a standard care only or a systematic pain assessment group. The Behavioral Pain Scale (BPS) and the Critical Pain Observation Tool (C-POT) were completed twice daily for all participants. In the intervention group, clinicians were notified of pain scores. Linear Mixed Models (LMM) for the longitudinal effect of the intervention were employed. Results: A total of 117 patients were included (control: n=61; intervention: n2=56). The incidence of pain (C-POT >2) in the intervention group was significantly lower compared to the control group (p < .001). The intervention had a statistically significant effect on pain intensity (BPS, p = 0.01). The average total morphine equivalent dose in the intervention group was higher than in the control group (p = 0.045), as well as the average total dose of propofol (p = 0.027). There were no statistically significant differences in ICU mortality (23.4% vs 19.3%, p=0.38, odds ratio 0.82 [0.337-1.997]) and length of ICU stay (13.5, SD 11.1 vs 13.9, SD 9.5 days, p= 0.47). Conclusion: Systematic pain assessment may be associated with a decrease in the intensity and incidence of pain and influence the pharmacological management of pain and sedation of critically ill patients.
Keywords: Pain assessment; Critical illness; Outcomes; Incidence of pain